La controverse de Didier Raoult et de sa proposition thérapeutique contre la COVID-19 sur Twitter : analyse de réseaux et de discours - Nikos Smyrnaios; Panos Tsimboukis; Lucie Loubère (Communiquer)
We propose to analyze both the network of actors and the network of the discourses mobilized in the controversy around Professor Didier Raoult and his Hydroxychloroquine-based therapeutic proposal against COVID-19. In order to confirm our hypothesis, we implement a sophisticated and innovative research method on a corpus of 1.2 million Tweets, which consists in applying a network analysis combined with a lexicometrics analysis. We show that the reaction peaks on Twitter were linked to important media events. Moreoever, many groups clustered around the accounts of political figures and media outlets that received numerous mentions. Trump's and Bolsonaro's supporter groups also connected with the French-speaking pro-Raoult groups. The messages of the pro-Raoult are a critique of the political economy of liberasim and its impasses, and not simply an anti-science conspiracy.